Question
upstudy study bank question image url

Given \( v=10 i+6 j \) and \( w=-i+1 \). a. Find prosw b. Decompose \( v \) into two vectors \( v_{1} \) and \( v_{2} \), where \( v_{1} \) is parallel to \( w \) and \( v_{2} \) is orthogonal to \( w \) a. projw \( v=\square \) (Type your answer in terms of \( i \) and \( j \).) b. \( v_{1}=\square \) (Type your answer in terms of \( i \) and \( j \).) \( v_{2}=\square \) (Type your answer in terms of \( i \) and \( j \).)

Ask by Gross Frazier. in the United States
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a. proj₍w₎ v = 2i – 2j b. v₁ = 2i – 2j v₂ = 8i + 8j

Solution

We are given   v = 10 i + 6 j   w = –i + j. Step 1. Compute the projection of v onto w (proj₍w₎ v). Recall the formula for projection of v onto w:   proj₍w₎ v = ((v · w)/(w · w)) w 1. Calculate the dot products:   v · w = (10)(–1) + (6)(1) = –10 + 6 = –4.   w · w = (–1)² + (1)² = 1 + 1 = 2. 2. Compute the scalar multiplier:   (v · w)/(w · w) = (–4)/(2) = –2. 3. Write the projection vector:   proj₍w₎ v = –2 · (–i + j) = 2 i – 2 j. Thus, the answer for part (a) is:   proj₍w₎ v = 2 i – 2 j. Step 2. Decompose v into two components v₁ and v₂ such that:   v₁ is parallel to w (v₁ = proj₍w₎ v)   v₂ is orthogonal to w (v₂ = v – v₁) We have already determined:   v₁ = proj₍w₎ v = 2 i – 2 j. Now, subtract v₁ from v to find v₂:   v₂ = v – v₁ = (10 i + 6 j) – (2 i – 2 j) = (10 – 2) i + (6 + 2) j = 8 i + 8 j. Thus, the answers are: a. proj₍w₎ v = 2 i – 2 j b. v₁ = 2 i – 2 j  v₂ = 8 i + 8 j.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve this problem, we need to approach parts (a) and (b) step-by-step. ### a. Find the projection of \( v \) onto \( w \) The projection of vector \( v \) onto vector \( w \) is given by the formula: \[ \text{proj}_w v = \frac{v \cdot w}{w \cdot w} w \] First, we calculate the dot products: - \( v \cdot w = (10i + 6j) \cdot (-i + 1j) = 10(-1) + 6(1) = -10 + 6 = -4 \) - \( w \cdot w = (-i + j) \cdot (-i + j) = (-1)(-1) + (1)(1) = 1 + 1 = 2 \) Now substituting back into the projection formula: \[ \text{proj}_w v = \frac{-4}{2} w = -2w = -2(-i + j) = 2i - 2j \] So, the answer for part (a) is: \[ \text{proj}_w v = 2i - 2j \] ### b. Decomposing \( v \) into \( v_1 \) and \( v_2 \) From the results above, we found \( v_1 \) as the projection of \( v \) onto \( w \): \[ v_1 = 2i - 2j \] To find \( v_2 \), we simply subtract \( v_1 \) from \( v \): \[ v_2 = v - v_1 = (10i + 6j) - (2i - 2j) = (10i - 2i) + (6j + 2j) = 8i + 8j \] So, the answers for part (b) are: \[ v_1 = 2i - 2j \] \[ v_2 = 8i + 8j \] ### Final Answers a. \(\text{proj}_w v = 2i - 2j\) b. \(v_1 = 2i - 2j\), \(v_2 = 8i + 8j\)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy